FAKTOR - FAKTOR PENYEBAB TERJADINYA KEKERASAN SEKSUAL TERHADAP ANAK DI KOTA MEDAN UU RI NO. 23 TAHUN 2002 DAN UU NO. 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - SYAHRIZAL EFENDI LUBIS (LP2MTBM MAKARIOZ, 2021)
Formulation of the problem is what are the factors that cause sexual violence against children in the city of Medan and howthe legal regulation of sexual violence crimes committed by children and how the application of the law against sexualviolence crimes committed by children based on the Decision of the Medan District Court No. 65/Pid.Sus-Anak/2017/PNMedan.The data used in this study is Secondary data. Discussed in this study is the existence of violence against girls thatbecome a serious threat to the growth and protection of children in Sumatra Uttara. Child and women's violence has reachedan emergency stage and requires the actions and participation of all parties including parents to combat it. The conclusion tothis research of the factors causing sexual violence is increasing inseparable from technological advances and globalissasi.The advice is that parents should limit the apps that can be downloaded by utilizing the android app lock feature to protectthe child from pornographic content that can damage the child's mental desire to commit sexual crimes. It can also be a wayof protecting children from various threats both from outside and from within themselves, educating, fostering, accompanyingchildren in various ways, preventing hunger and working on their health, and by providing self-support for children.